Energy productivity through herbicidal weed control in soybean (Glycine max) - BILLORE, S D; JOSHI, O P; RAMESH, A (The Indian Journal of Agricultural Sciences, 2013)
Afield experiment was conducted during rainy season of 1996 and 1997 to study the energy productivity through post-emergence weedicides in comparision to pre-emergence and pre-plant incorporation weedicides and cultural practices on soybean (Glycine max (L.)Merr.). Application of post-emergence weedicides (imazethapyr, propaquizafop and fenaxyprop-p-ethyl) were found equally effective in controlling weeds of soybean as pre-emergence (alachlor and pendimethalin), pre-plant incorporation (trifluralin) and 2 hand weedings as evidenced from the yield data. Application of anilophos followed by alachlor and 2 hand weedings consumed maximum energy input. The application of preemergence and pre- plant incorporation weedicides was inferior to post-emergence weedicides with respect to energy output, energy-use efficiency, energy productivity and labour productivity. The weedy check and application ofanilophos were the most energy intensive